The Role of the Social Researcher in Addressing Students’ Problems in Non-Governmental Schools - Mahmoud, Muhammad Yousif Mahmoud (Sulaimani Journal for Humanities, 2026)
Through adopting the descriptive method and conducting eleven semi-structured interviews, this study aimed to shed light on the role of the social researcher in addressing students’ problems in non-governmental schools. Through several key questions, the study sought to answer: What role do researchers play in non-governmental schools? To what extent do they possess the scientific knowledge required to address students’ problems? And what obstacles do researchers face in solving these problems? The study found that researchers play an effective role in addressing students’ problems. While some researchers lack the scientific basis in their approach, most follow organized and systematic scientific steps. The results also indicate the presence of several obstacles facing researchers in this area, such as the lack of cooperation from some students’ families with the researcher and the school in addressing the problems, as well as the nature of the problems and their impact on family responsiveness. Furthermore, the school’s operational framework and system pose challenges to the researcher’s methods and the approach to solving students’ problems.